Redescription of Vieja hartwegi (Taylor & Miller 1980) (Teleostei: Cichlidae) from the Grijalva River basin, Mexico and Guatemala, with description of a rheophilic morph - Gómez-González, Adán E.; Álvarez, Fernando; Matamoros, Wilfredo A.; Velázquez-Velázquez, Ernesto; Schmitter-Soto, Juan J.; González-Díaz, Alfonso A.; Mcmahan, Caleb D. (Zootaxa, 2018)
Vieja hartwegi was described by Taylor and Miller in 1980 based on 45 juvenile and sub-adult specimens, but this species shows an enormous variation in coloration patterns during ontogenic development and between individuals. Additionally, morphological data have demonstrated the existence of two forms in V. hartwegi: the typical morph of a moderately deep to slightly elongated body shape with midlateral band, and a rheophilic morph with an elongated to slightly deep body shape and lack of midlateral band. Herein we redescribe V. hartwegi adding adults and individuals from broad geographic ranges, as well as a rheophilic morph recently discovered in the upper reaches of the Grijalva River basin in Mexico. The set of characters include coloration, meristic, morphometric and osteological features. Vieja hartwegi is a polymorphic species whose forms may be segregating because of habitat preferences and food habits.